2008
DOI: 10.1073/pnas.0803379105
|View full text |Cite
|
Sign up to set email alerts
|

Drug-sensitiveFGFR2mutations in endometrial carcinoma

Abstract: Oncogenic activation of tyrosine kinases is a common mechanism of carcinogenesis and, given the druggable nature of these enzymes, an attractive target for anticancer therapy. Here, we show that somatic mutations of the fibroblast growth factor receptor 2 (FGFR2) tyrosine kinase gene, FGFR2, are present in 12% of endometrial carcinomas, with additional instances found in lung squamous cell carcinoma and cervical carcinoma. These FGFR2 mutations, many of which are identical to mutations associated with congenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
283
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 326 publications
(296 citation statements)
references
References 44 publications
11
283
0
1
Order By: Relevance
“…The frequency of FGFR2 mutations in this series (6.45%) is a little bit lower than that of previous series (10-12%). [13][14][15] However, the number of cases tested for FGFR2 mutations is smaller than that of other series. It is worth mentioning that our series has the additional value that the cases had been previously tested for microsatellite instability, as well as mutations of KRAS, PTEN, PIK3CA and CTNNB1.…”
Section: Fgfr2 Mutationsmentioning
confidence: 90%
See 2 more Smart Citations
“…The frequency of FGFR2 mutations in this series (6.45%) is a little bit lower than that of previous series (10-12%). [13][14][15] However, the number of cases tested for FGFR2 mutations is smaller than that of other series. It is worth mentioning that our series has the additional value that the cases had been previously tested for microsatellite instability, as well as mutations of KRAS, PTEN, PIK3CA and CTNNB1.…”
Section: Fgfr2 Mutationsmentioning
confidence: 90%
“…Moreover, somatic mutations in the receptor tyrosine kinase FGFR2, identical to the germline mutations associated with craniosynostosis and skeletal dysplasia syndromes, have been recently detected in 10-12% of endometrial carcinomas, particularly in endometriod endometrial carcinomas (16%). [13][14][15] The somatic mutations included the S252W and P235R changes, which are associated with the Apert syndrome, the N549K and K659M, which are associated with Crouzon syndrome, as well as the N550K change. 31 Interestingly, FGFR2 and K-RAS FGFR2 in endometrial cancer mutations were mutually exclusive events, whereas mutations in FGFR2 and PTEN frequently coexisted.…”
Section: Fgfr2 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the targetable S252W mutation has been found that in 12% of endometrial cancer cells (Dutt et al, 2008).…”
Section: Gene Mutationmentioning
confidence: 99%
“…96 Other oncogenes have also been reported as altered in endometrial cancer; Drug sensitive mutations in the fibroblast growth factor receptor 2 (FGFR2) tyrosine kinase gene have been reported in 12% of endometrial carcinomas. 119 Nuclear accumulation of ȕ-catenin (CTNNB1), only partially explained by mutations, is detected more frequently in Type I compared to Type II cancers. 120 Growth differentiation factor-15…”
Section: Stathminmentioning
confidence: 99%